AB0507 Health-related quality of life (HRQOL) benefits associated with reductions in disease activity and pain severity among rheumatoid arthritis (RA) patients treated with secukinumab. (23rd January 2014) - Gnanasakthy, A.; Kosinski, M.; Genovese, M.; Mallya, U.; Mpofu, S.
Abstract : Background: The aim of RA treatment is to reduce disease activity and pain. In this study we explore the association between HRQoL and reductions in disease activity and pain from RA treatment. Objectives: To evaluate the HRQoL benefits associated with reductions in disease activity and pain among RA patients treated with secukinumab in a phase 2 randomized controlled trial. Methods: Adult RA patients (n=237) on methotrexate were randomized equally to receive monthly s.c. injections of secukinumab 25mg, 75mg, 150mg, 300mg or placebo. Secondary efficacy endpoints consisted of physician (PH-GADA) and patient (PT-GADA) global ratings of disease activity and VAS pain severity ratings, each measured using a 0-100 scale. HRQoL was assessed using the SF-36v2 Health Survey, the Health Assessment Questionnaire-Disability Index (HAQ-DI), and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue). Changes from baseline to week 16 were calculated for secondary endpoints and HRQoL measures. Patients treated with secukinumab were categorized into responder (improvement of >10 points) and non-responder groups (improvement <10 points) on each secondary endpoint measure. Analysis of variance was used to test differences in mean changes in HRQoL scores across responder and non-responder groups on each secondary efficacy endpoint. Results: One-half or more patients showed clinically meaningful reduction on the PT-GADA (50%) and PH-GADA (71%) and 46% showed clinically meaningful reduction in pain severity. In general, statistically significant and meaningful changes in HRQoL scores were observed among responders on each secondary efficacy measure. Among PT-GADA responders, relatively small improvements of 11 to 20 points was associated with significant and meaningful improvements on most HRQoL scales ranging from 1.4 to 4.9 points across SF-36v2 scales, 5.9 points on FACIT-Fatigue, and -0.32 on HAQ-DI. Patients showing a greater improvement (>20 points) on the PT-GADA showed incrementally larger improvement in HRQoL scores across all SF-36v2, FACIT-Fatigue, and HAQ-DI scales. Significant and meaningful improvement in HRQoL scores required larger improvement in PH-GADA ratings (>20 points) compared to PT-GADA. The range of score improvement was 1.7 to 5.9 points across SF-36 scales, 4.1 points on FACIT Fatigue, and -0.28 points on HAQ-DI. Lastly, statistically significant and meaningful improvement in HRQoL scores was observed among patients showing clinically meaningful reduction in pain. Mean score improvement ranged from 3.8 to 8.9 points across SF-36v2 scales, 7.2 points on FACIT-Fatigue, and -0.47 points on HAQ-DI among pain responders. Conclusions: In patients treated with secukinumab, greater reduction in disease activity and pain severity was associated with clinically relevant HRQoL benefits. The implications of this response should be further investigated in future trials. Disclosure of Interest: A. Gnanasakthy Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, M. Kosinski Consultant for: Novartis Pharmaceuticals Corporation, M. Genovese Grant/Research support from: Novartis, U. Mallya Employee of: Novartis Pharmaceuticals Corporation, S. Mpofu Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG